Patients' Knowledge of and Practices Relating to the Disposal of Used Insulin Needles - Kerri T. Musselman; Brigitte L. Sicat; Michelle Herbert Thomas; Spencer E. Harpe (University of Minnesota Libraries Publishing, 2010)
Objective: To determine (1) how patients currently dispose of used insulin needles, (2) whether patients were educated about disposal of their used insulin needles, and (3) who educated patients about the disposal of their used insulin needles. Methods: A self-administered questionnaire was designed for this study. The survey assessed patient knowledge about disposal of used insulin needles and the patient-reported source and location of education about disposal techniques. The questionnaire was administered to a convenience sample of patients from four locations in Richmond, Virginia. Any patient who used insulin, was at least 18 years old, and was willing to complete the survey was eligible for inclusion. Results: Fifty responses were received with 40% indicating that education had been received on the disposal of used needles. From that 40%, nurses were identified as the source of education 60% of the time and pharmacists 25% of the time. Approximately 50% of the respondents reported disposing of used needles directly in the trash when at home. While away from home, 22% reported placing used needles in the trash, and 38% took them home for disposal. Conclusion: Patients are not consistently educated regarding the proper disposal of used needles. Health care practitioners should play a larger role in educating patients about the potential risks of inappropriate needle disposal and appropriate disposal methods. Future research is still needed to understand fully the magnitude of the problems associated with inappropriate needle disposal by patients. Type: Original Research